Aged polyethylene microplastics and glyphosate-based herbicide co-exposure toxicity in Pacific white shrimp (Litopenaeus vannamei) - Thammatorn, Worrayanee; Cholewińska, Paulina; Kruangkum, Thanapong; Palić, Dušan (Frontiers in Marine Science, 2024)
Microplastics and glyphosate-based herbicides (GBHs) unavoidably contaminate aquatic environments, yet their combined effect on aquatic organisms has been scarcely investigated. We present a short-term study on individual and combined effects of aged polyethylene (PE) microplastics and GBH exposures at environmentally relevant concentrations on oxidative damage, antioxidant responses, immune parameters, and hepatopancreas histology in shrimp (Litopenaeus vannamei). In addition, acetylcholinesterase (AChE) was evaluated as a biomarker of GBH exposure. After 96 hours of exposure, individual PE microplastic exposure slightly influenced oxidative status, immune parameters, and histology. Decreases in AChE concentration and alterations in oxidative status, immunity, and cell population in hepatopancreas were observed in single GBH-exposed shrimp. The combinations of aged PE microplastics and GBH induced some changes that differed from individual GBH exposures. For instance, some alterations implied that the presence of aged PE microplastics may alter GBH toxicity to L. vannamei (AChE concentration and some expressions of immune-related genes). In conclusion, our results suggest that single exposure of aged PE microplastics at environmental concentration may slightly affect the health of L. vannamei and that aged PE microplastics are likely to modify the toxicity of other co-exposed chemicals.